Diaphragm and preparation method thereof, battery and electric device
Patent Information
- Application Number
- CN202380051160.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-01-06
- Publication Date
- 2025-02-18
AI Technical Summary
Existing safety-modified separators have poor pressure resistance during battery production and normal operation, affecting breathability and electrochemical performance. They are also difficult to effectively close pores when thermal runaway occurs, reducing battery safety performance.
A coating is placed on the base film. The coating contains polymer particles with branched carbon numbers from 1 to 10. By adjusting the polymer molecular weight, polydispersity index and non-ionic group content, the coating's mechanical properties such as pressure resistance are improved. , and melt and seal the pores of the base film when the temperature rises abnormally, reducing the risk of thermal runaway.
It improves the mechanical properties such as pressure resistance and breathability of the separator, ensures the stability and safety of the battery under pressure and thermal abnormalities, reduces the risk of thermal runaway, and improves the electrochemical performance and safety performance of the battery.
Smart Images

Figure CN119487685A_ABST
Abstract
Description
Diaphragm and preparation method thereof, battery and electrical device Technical Field
[0001] The present application relates to the field of battery technology, and in particular to a diaphragm and a preparation method thereof, a battery and an electrical device. Background Art
[0002] In the context of energy conservation and emission reduction, new energy technologies are developing rapidly, among which the research breakthroughs and applications of battery technology are the most significant, and lithium-ion batteries are the battery with the most prominent development momentum.
[0003] As battery applications expand, especially in recent years with the rapid development of electric vehicles, power batteries have experienced rapid development and a sharp increase in demand. However, battery safety performance has also received increasing attention and has become one of the key factors restricting the expansion of battery applications.
[0004] Among battery safety issues, the most prominent is the runaway exothermic reaction within the battery. While the emergence of safety-modified diaphragms can improve their safety against thermal runaway to a certain extent, this also results in relatively poor compressive strength when subjected to external pressure during battery production or normal operation. This affects the diaphragm's gas permeability, thereby reducing the permeability of the electrolyte and thus affecting the electrochemical performance of the battery during production and normal operation.
[0005] Summary of the Invention
[0006] In view of the above problems, the embodiments of the present application provide a diaphragm and a preparation method and application thereof to solve the technical problem of poor pressure resistance of existing safety modified diaphragms.
[0007] In a first aspect, embodiments of the present application provide a separator comprising a base film and a coating disposed on at least one surface of the base film, wherein the coating contains polymer particles, and the number of carbon atoms in the branched chains of the polymer contained in the polymer particles is 1 to 10.
[0008] The coating of the diaphragm in the embodiment of the present application contains polymer particles with this branched carbon number range, which gives the coating a good air permeability and higher mechanical properties such as compressive strength. It can maintain the good air permeability of the diaphragm under pressure, thereby maintaining the permeability of the diaphragm to the electrolyte and the stability of its operation, thereby ensuring the stable electrochemical performance of the battery. Moreover, when the battery is abnormally heated to its melting point, the polymer particles in this branched carbon number range can melt, thereby sealing the pores contained in the base film, preventing or reducing chemical reactions inside the battery, including crosstalk reactions between the positive and negative electrodes, thereby reducing the risk of thermal runaway of the battery and improving battery safety performance.
[0009] In some embodiments, the polymer satisfies at least one of the following conditions (1) to (3):
[0010] (1) The weight average molecular weight of the polymer is 1500 to 5000, and can be optionally 1500 to 2500.
[0011] (2) the polydispersity index (PDI) of the polymer is from 3 to 11, optionally from 3 to 6;
[0012] (3) The number of carbon atoms in the branched chain of the polymer is 1 to 5.
[0013] By further adjusting and selecting the polymer molecular weight, PDI, and branched carbon number, the mechanical properties of the above-mentioned polymer particles, including compressive strength, can be further improved, and the mechanical properties of the coating, including compressive strength, can be improved, thereby improving the electrolyte permeability and working stability of the diaphragm when it is subjected to pressure during battery production and normal operation, and at the same time improving the hot melt response rate of the diaphragm when thermal anomalies occur in the battery.
[0014] In some embodiments, the polymer particles contain nonionic groups. In exemplary embodiments, the nonionic groups include at least one of ethoxy, hydroxyl, and carboxylate groups. The polymer particles' material containing nonionic groups, specifically these types of nonionic groups, not only improves the polymer's hydrophilicity and dispersibility, but also further enhances the aforementioned mechanical properties of the polymer particles, such as compressive strength, thereby improving the coating quality and mechanical properties, such as compressive strength, and thereby enhancing the permeability and operational stability of the diaphragm under pressure.
[0015] In some embodiments, the content of the polymer particles in the coating is ≥ 22 wt%, and can be optionally 22 wt% to 37 wt%, based on the total dry weight of the coating as 100%. By controlling and adjusting the content of the polymer particles in the coating, the compressive and other mechanical properties of the coating can be improved, thereby improving the compressive and other mechanical properties and operational stability of the diaphragm. The diaphragm can also be accelerated in its melting response rate to abnormal heat rise, and the effectiveness of the molten polymer particles in sealing the pores of the base membrane can be enhanced.
[0016] In some embodiments, the polymer particles satisfy at least any one of the following conditions (1) to (4):
[0017] (1) Volume distribution particle size D of the polymer particles v 50 is 0.1μm to 5μm;
[0018] (2) The melting point of the polymer particles is 100°C to 110°C;
[0019] (3) The polymer particles are in at least one of the following shapes: chain, spherical, quasi-spherical, fibrous, tubular, rod-like, amorphous, and pyramidal;
[0020] (4) The polymer includes at least one of polystyrene, polyethylene, polyimide, melamine resin, phenol resin, cellulose, cellulose modifier, polypropylene, polyester, polyphenylene sulfide, polyaramid, polyamideimide, polyimide, and a copolymer of butyl acrylate and ethyl methacrylate.
[0021] The polymer particles have any of the above characteristics and can improve the mechanical properties of the coating such as air permeability and compressive resistance, thereby improving the air permeability and working stability of the diaphragm, while further reducing the risk of thermal runaway of the battery and improving the electrochemical properties and safety performance of the battery such as capacity retention rate.
[0022] In some embodiments, the coating further comprises an inorganic particle filler. The presence of the inorganic particle filler can further improve the air permeability and mechanical properties such as compressive strength of the coating, thereby improving the air permeability and working stability of the diaphragm.
[0023] In some embodiments, the inorganic particulate filler satisfies at least one of the following conditions:
[0024] The content of the inorganic particulate filler in the coating is 18 wt % to 22 wt % based on the total dry weight of the coating as 100%;
[0025] The volume distribution particle size D of the inorganic particle filler v 50 is 1 to 1.5 μm;
[0026] The inorganic particle filler includes at least one of inorganic particles having a dielectric constant of 5 or greater, inorganic particles having ion conductivity but not storing ions, and inorganic particles capable of undergoing electrochemical reactions.
[0027] The inorganic particle filler has any of the above characteristics and can further improve the mechanical properties such as air permeability and compressive resistance of the coating, thereby improving the air permeability and working stability of the diaphragm.
[0028] In some embodiments, the coating further comprises a solidified aqueous binder. By adding the aqueous binder to the coating, the mechanical strength of the diaphragm can be improved, and the air permeability and working stability of the diaphragm can be adjusted.
[0029] In the embodiment, the aqueous binder satisfies at least any one of the following conditions:
[0030] The cured aqueous binder has a dry weight content of 18 wt % to 27 wt % in the coating;
[0031] The thermal decomposition temperature of the aqueous binder is higher than 160°C.
[0032] The aqueous binder has any of the above characteristics, can enhance the mechanical strength of the diaphragm, and further adjust the working stability of the diaphragm.
[0033] In some embodiments, the coating has a thickness of 2 μm to 5 μm.
[0034] By controlling the coating thickness, the mechanical properties of the coating, i.e. the diaphragm, such as air permeability and compressive resistance, can be improved, thereby improving the electrochemical performance of the battery and reducing or preventing the risk of thermal battery runaway.
[0035] In some embodiments, the base film satisfies at least one of the following conditions:
[0036] The base film has a thickness of 4 μm to 7 μm;
[0037] The air permeability of the separator is 180s / 100cc to 240s / 100cc.
[0038] The base film with these characteristics can fully play the role of the battery separator and improve the mechanical properties such as compressive resistance and working stability of the separator.
[0039] In a second aspect, an embodiment of the present application provides a method for preparing a diaphragm. The method for preparing a diaphragm in an embodiment of the present application comprises the following steps:
[0040] Providing a base film and a coating slurry containing polymer particles; the polymer particles contain a polymer having a branched carbon number of 1 to 10;
[0041] The coating slurry is coated on at least one surface of the base film, and dried to form a coating layer to obtain a separator.
[0042] The diaphragm prepared by the diaphragm preparation method of the embodiment of the present application has mechanical properties such as high compressive resistance and good air permeability as the diaphragm of the embodiment of the text application above, and can effectively reduce the risk of thermal runaway of the battery and improve the electrochemical performance and safety of the battery.
[0043] In some embodiments, the coating slurry is formed by mixing polymer particles, inorganic particle fillers and aqueous binders in a solvent; wherein the mass ratio of the polymer particles, inorganic particle fillers and aqueous binders in the coating slurry is (22 to 37):18 to 22):(18 to 27).
[0044] In some embodiments, the coating slurry has a solid content of 30 wt % to 40 wt %.
[0045] In some embodiments, the coating slurry has a viscosity of 100 mPa·s to 1000 mPa·s at 25°C.
[0046] The coating slurry with the above characteristics can improve the film-forming quality, the quality of the coating, and the properties such as air permeability and pressure resistance.
[0047] In some embodiments, when the polymer particles are polymer particles containing nonionic groups, the polymer particles are prepared by a method comprising the following steps:
[0048] The polymer precursor particles, the ethoxy-containing polymer and the initiator are mixed and reacted to obtain polymer particles containing nonionic groups;
[0049] The polymer particles containing nonionic groups are emulsified with a nonionic surfactant to obtain a nonionic polymer emulsion.
[0050] By using ethoxylated polymers to carry out polymerization reactions with polymer precursor particles, the non-ionic groups contained in the polymer particles can be increased, especially the mechanical properties of the polymer particles such as compressive strength can be improved, while the dispersion of the polymer particles in the coating slurry can be improved, thereby improving the film-forming quality and mechanical properties such as compressive strength of the coating slurry, thereby improving the mechanical properties and working stability of the diaphragm.
[0051] In some embodiments, the polymer precursor particles, the ethoxy-containing polymer, and the initiator are mixed in a ratio of (300 to 400): (90 to 125): (20 to 50).
[0052] In some embodiments, the material of the polymer precursor particles includes at least one of polystyrene, polyolefin, polyimide, melamine resin, phenol resin, cellulose, polyester, polyphenylene sulfide, polyaramid, polyamideimide, and a copolymer of butyl acrylate and ethyl methacrylate.
[0053] In some embodiments, the ethoxy-containing polymer includes at least one of allyl polyethylene glycol and bisallyl polyether.
[0054] In some embodiments, the initiator includes at least one of di-tert-butyl peroxide and dicumyl peroxide.
[0055] In some embodiments, the reaction temperature is 130°C to 140°C.
[0056] In some embodiments, the polymer particles and the nonionic surfactant are emulsified in a mass ratio of (4 to 6):1.
[0057] The types and mixing ratios of the reactants and the reaction conditions mentioned above can increase the grafting rate and content of the nonionic groups of the polymer particles, and improve the mechanical properties of the polymer particles such as compression resistance and the dispersibility in the coating slurry.
[0058] In the embodiment, the nonionic polymer emulsion satisfies at least any one of the following conditions (1) to (4):
[0059] (1) The viscosity of the nonionic polymer emulsion at 25° C. is 10 mPa·s to 100 mPa·s;
[0060] (2) the solid content of the nonionic polymer emulsion is 35 wt% to 40 wt%;
[0061] (3) the pH value of the nonionic polymer emulsion is 5 to 6;
[0062] (4) The nonionic surfactant includes a molecular structure of Wherein, R1 is a carbon chain alkyl group, R2 is a hydrophilic group, and n is a positive integer from 3 to 20.
[0063] In an exemplary embodiment, the carbon chain alkyl group is a long carbon chain alkyl group ranging from C12 to C18.
[0064] In an exemplary embodiment, R2 is at least one of a carboxyl group, an amine group, an aldehyde group, an alcohol group, an amino group, and an amide group.
[0065] In an exemplary embodiment, the nonionic surfactant includes at least one of fatty alcohol polyoxyethylene ether, alkylphenol polyoxyethylene ether, fatty acid polyoxyethylene ester, castor oil polyoxyethylene ether, fatty amine polyoxyethylene ether, sorbitan fatty acid ester, and polyoxyethylene sorbitan fatty acid ester.
[0066] By selecting the type of nonionic surfactant, the stability of the nonionic polymer emulsion can be improved, its dispersibility in the coating slurry can be improved, and thus the dispersion uniformity and stability of the polymer particles can be improved.
[0067] In some embodiments, the aqueous binder is added in the form of an aqueous binder solution, and the aqueous binder solution has at least one of the following conditions:
[0068] The viscosity of the binder aqueous solution at 25° C. is 3000 mPa·s to 10000 mPa·s;
[0069] The solid content of the binder aqueous solution is 40 wt % to 50 wt %.
[0070] In some embodiments, the coating slurry is applied at a rate of 20 m / min to 100 m / min.
[0071] In some embodiments, the drying temperature is 50°C to 70°C.
[0072] In some embodiments, the drying process lasts for 1 to 5 minutes.
[0073] By adjusting the coating process conditions, the film quality, thickness and permeability can be adjusted and optimized.
[0074] In a third aspect, embodiments of the present application provide a battery. The battery of the present application includes a positive electrode, a negative electrode, and a separator laminated between the positive and negative electrodes. The separator is the separator described in the embodiments of the present application or a separator prepared by the separator preparation method of the embodiments of the present application. Because the battery of the present application includes the separator of the embodiments of the present application, it has high battery safety and good electrochemical properties such as capacity retention.
[0075] In an embodiment, the coating is provided on one surface of the separator, with the coating facing the negative electrode. By only applying the coating to one surface of the separator, the overall thickness of the separator can be effectively reduced, thereby increasing the energy density of the battery.
[0076] Fourthly, embodiments of the present application provide an electrical device. The electrical device of the embodiment of the present application includes a battery according to the embodiment of the present application, the battery being used to provide electrical energy. The safety of the electrical device of the embodiment of the present application is significantly improved.
[0077] The above description is only an overview of the technical solution of the present application. In order to more clearly understand the technical means of the present application, it can be implemented in accordance with the contents of the specification. In order to make the above and other purposes, features and advantages of the present application more obvious and easy to understand, the specific implementation methods of the present application are listed below. BRIEF DESCRIPTION OF THE DRAWINGS
[0078] Various other advantages and benefits will become apparent to those skilled in the art upon reading the detailed description of the preferred embodiment below. The accompanying drawings are for illustration purposes only and are not to be considered as limiting the present application. The same reference numerals are used throughout the drawings to represent the same components. In the drawings:
[0079] FIG1 is a schematic flow chart of a method for preparing a diaphragm according to an embodiment of the present application;
[0080] FIG2 is a schematic structural diagram of an embodiment of a secondary battery according to an embodiment of the present application;
[0081] FIG3 is an exploded schematic diagram of the secondary battery shown in FIG2 ;
[0082] FIG4 is a schematic structural diagram of an embodiment of a battery module according to the present application;
[0083] FIG5 is a schematic structural diagram of an embodiment of a battery pack according to the present application;
[0084] FIG6 is a schematic diagram of the exploded structure of the battery pack shown in FIG5 ;
[0085] FIG. 7 is a schematic diagram of an embodiment of an electric device including a secondary battery according to an embodiment of the present application as a power source.
[0086] The accompanying drawings in the specific implementation manner are as follows:
[0087] 10. Secondary battery cell, 11. Housing, 12. Electrode assembly, 13. Cover plate;
[0088] 20. Battery module;
[0089] 30. Battery pack, 31. Box, 32. Lower box. DETAILED DESCRIPTION
[0090] The following embodiments of the technical solution of the present application will be described in detail with reference to the accompanying drawings. The following embodiments are only used to more clearly illustrate the technical solution of the present application and are therefore only examples and are not intended to limit the scope of protection of the present application.
[0091] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by those skilled in the art to which this application belongs; the terms used herein are only for the purpose of describing specific embodiments and are not intended to limit this application; the terms "including" and "having" and any variations thereof in the specification and claims of this application and the above-mentioned figure descriptions are intended to cover non-exclusive inclusions.
[0092] In the description of the embodiments of this application, the technical terms "first" and "second" are used only to distinguish different objects and should not be understood to indicate or imply relative importance or implicitly specify the quantity, specific order, or primary and secondary relationship of the indicated technical features. In the description of the embodiments of this application, the meaning of "plurality" is more than two, unless otherwise clearly and specifically defined.
[0093] References herein to "embodiments" mean that a particular feature, structure, or characteristic described in connection with the embodiments may be included in at least one embodiment of the present application. The appearance of this phrase in various places in the specification does not necessarily refer to the same embodiment, nor does it constitute an independent or alternative embodiment that is mutually exclusive of other embodiments. It is understood, both explicitly and implicitly, by those skilled in the art that the embodiments described herein may be combined with other embodiments.
[0094] In the description of the embodiments of this application, the term "and / or" is simply a description of the association relationship between associated objects, indicating that three relationships can exist. For example, A and / or B can represent the following three situations: A exists alone, A and B exist simultaneously, and B exists alone. In addition, the character " / " in this document generally indicates that the associated objects are in an "or" relationship.
[0095] In the description of the embodiments of the present application, the term "multiple" refers to more than two (including two). Similarly, "multiple groups" refers to more than two groups (including two groups), and "multiple pieces" refers to more than two pieces (including two pieces).
[0096] In the description of the embodiments of the present application, the technical terms "center", "longitudinal", "lateral", "length", "width", "thickness", "up", "down", "front", "back", "left", "right", "vertical", "horizontal", "top", "bottom", "inside", "outside", "clockwise", "counterclockwise", "axial", "radial", "circumferential", etc., indicating the orientation or position relationship, are based on the orientation or position relationship shown in the accompanying drawings, and are only for the convenience of describing the embodiments of the present application and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as a limitation on the embodiments of the present application.
[0097] In the description of the embodiments of the present application, unless otherwise expressly specified or limited, technical terms such as "installed," "connected," "connected," and "fixed" should be understood in a broad sense. For example, they can refer to fixed connections, detachable connections, or integration; mechanical connections or electrical connections; direct connections or indirect connections through an intermediate medium; internal connections between two components or interactions between two components. Those skilled in the art can understand the specific meanings of the above terms in the embodiments of the present application based on specific circumstances.
[0098] In the context of energy conservation and emission reduction, new energy technologies are developing rapidly, among which the research breakthroughs and applications of battery technology are the most significant, and lithium-ion batteries are the battery with the most prominent development momentum.
[0099] In ion batteries such as lithium-ion batteries, the diaphragm is one of the important components, which is set between the positive and negative pole pieces to separate the positive and negative poles of the battery, preventing the two poles from contacting and short-circuiting, and preventing the Li-ion battery from passing through the positive and negative poles. + Therefore, in addition to having good electrolyte wettability, liquid retention, and mechanical strength, the separator also needs to have properties such as thermal stability that have a significant impact on battery safety, as battery safety performance is increasingly valued.
[0100] Currently, the method of improving the thermal stability and other properties of the diaphragm is to modify the diaphragm, such as doping or coating modifiers such as flame retardant additives, fiber-like substances, electrochemically inert ceramics, etc. during the preparation process of the diaphragm, so as to achieve the purpose of improving the thermal stability and other properties of the diaphragm and thus improving battery safety.
[0101] While current methods like doping or coating can improve separator performance, such as thermal stability, to a certain extent, the inventors discovered that when exothermic reactions within the battery accumulate to a certain level, the modified separator is unable to promptly block the continued reaction. This makes it difficult to slow the exothermic reaction and reduce the possibility of internal short circuits or even thermal runaway. Therefore, these methods are not ideal for improving battery safety, such as thermal runaway.
[0102] In order to improve the role of the diaphragm in suppressing battery thermal runaway, the surface of the diaphragm is currently modified, such as adding a modified coating. However, the inventors found in their research that adding a modified coating to the diaphragm actually has an adverse effect on the air permeability of the diaphragm. Therefore, the inventors proposed a modified diaphragm, specifically adding a coating containing polymer particles to the base membrane of the modified diaphragm, which ensures good air permeability of the diaphragm and has good air permeability during normal production and use of the battery; when overheating occurs inside the battery, the coating can also melt and seal the pores of the base membrane in time to form a blocking barrier layer, reducing or completely blocking the reaction inside the battery, thereby reducing the risk of thermal runaway of the battery and improving the safety performance of the battery.
[0103] Based on this, the inventors further discovered that by further selecting or modifying the polymer particles contained in the modified separator coating, the coating's mechanical properties, such as compressive strength, can be further improved while ensuring good air permeability and effectively reducing the risk of thermal runaway. This allows the separator to maintain good air permeability when subjected to pressure during assembly and normal operation, ensuring normal function and fully utilizing its functions, thereby improving the battery's electrochemical properties, such as cycling performance. Therefore, based on the previous separator modification scheme, the following separator improvement scheme is further proposed.
[0104] diaphragm
[0105] In a first aspect, embodiments of the present application provide a separator. The separator includes a base membrane and a coating disposed on at least one surface of the base membrane. The coating contains polymer particles, wherein the polymer particles contain a polymer having a branched carbon number of 1 to 10.
[0106] In the diaphragm of the embodiment of the present application, the base film contained therein constitutes the matrix of the diaphragm of the embodiment of the present application and plays the usual role of the diaphragm. The coating is provided on the base film, which modifies the base film, that is, the diaphragm matrix. The branched carbon number can indicate the "branching degree" of the polymer, which refers to the number of carbon atoms on the branched chain of the polymer. The branched carbon number can be tested using nuclear magnetic resonance. The smaller the branched carbon number data, the more linear the polymer molecular structure is and the fewer branches are.
[0107] Since the polymer particles contained in the coating of the diaphragm of the embodiment of the present application exist in a particle morphology, and the number of branched carbons of the polymer material is in the range of 1 to 10, the polymer particles are given both high compressive strength and sensitive hot melt response performance. In this way, when the diaphragm is used in a battery, it can ensure that the battery has high compressive strength when subjected to pressure during production and normal operation, maintain the good air permeability and working stability of the diaphragm, and give the battery good electrochemical properties. When the battery is abnormally heated to the melting point of the polymer particles, the polymer particles can melt to close the pores contained in the base film, and the diaphragm plays a barrier role, thereby effectively reducing or preventing the chemical reactions inside the battery, including the chemical reactions in the electrolyte, the migration of metal ions, and the positive and negative electrode crosstalk reactions. Among them, the migration of the metal ions includes lithium ions and metal precipitation from active materials, etc., to prevent them from passing through the diaphragm and depositing on the surface of the electrode, especially the negative electrode, or further forming dendrites. The positive-negative electrode crosstalk reaction refers to the release of oxygen when the positive electrode active material of the battery undergoes a phase change at high temperature. The oxygen can diffuse to the negative electrode through the diaphragm and react with the negative electrode, etc., and release a large amount of heat; it also includes the hydrogen released from the negative electrode at high temperature, which diffuses to the positive electrode through the diaphragm and reacts with the positive electrode, etc., and releases a large amount of heat.
[0108] Therefore, the presence of polymer particles in the coating contained in the diaphragm of the present application, and the number of side chain carbons of the polymer material of the polymer particles is controlled in the range of 1 to 10, on the one hand, gives the coating, that is, the diaphragm containing the coating, good air permeability, which can ensure the pressure resistance of the diaphragm during battery production and normal operation, thereby having good air permeability, ensuring and improving the migration efficiency of ions between the positive and negative electrodes, thereby ensuring the normal electrochemical performance of the battery. If the number of side chain carbons of the polymer is higher than 10, it will lead to a decrease in the mechanical properties of the polymer particles, such as the pressure resistance; at the same time, it will also cause the melting point of the polymer particles to increase, and the hot melt response rate will also decrease accordingly. This will increase the hot melt response temperature range of the diaphragm and relatively reduce the hot melt response rate of the diaphragm. If the temperature of the battery rises abnormally due to thermal abnormality, the melting rate of the polymer particles will decrease, reducing the rate of sealing the pores of the base membrane, thereby reducing the response rate of the diaphragm to the thermal runaway of the battery.
[0109] In some embodiments, the polymer of the polymer particles may further be selected to satisfy at least any one of the following characteristics (1) to (3):
[0110] (1) The weight average molecular weight of the polymer may be 1500 to 5000, and optionally 1500 to 2500;
[0111] (2) the polydispersity index (PDI) of the polymer may be from 3 to 11, and optionally from 3 to 6;
[0112] (3) The number of carbon atoms in the polymer branch chain is further 1 to 5.
[0113] The polydispersity index (PDI) is calculated as weight-average molecular weight / number-average molecular weight. A lower value indicates a narrower molecular weight distribution. The PDI can be measured using conventional methods.
[0114] By further selecting the polymer molecular weight, polydispersity index PDI and branched carbon number, the mechanical properties of the above-mentioned polymer particles, including compressive strength, can be further improved, thereby further improving the compressive strength and other mechanical properties of the coating, that is, the diaphragm in battery production and normal operation, and improving the permeability and stability of the diaphragm in a normal working environment, thereby improving the stability of the electrochemical performance of the battery in normal operation. At the same time, the diaphragm's hot melt response rate to battery thermal anomalies further reduces or avoids the risk of thermal runaway of the battery.
[0115] In some embodiments, the morphology of the polymer particles contained in the coating can include at least one of chain, spherical, quasi-spherical, fibrous, tubular, rod-shaped, amorphous, and pyramidal shapes. Combined with the aforementioned branched carbon number or molecular weight of the polymer particles ranging from 1500 to 5000 and a PDI of 3 to 11, polymer particles with these morphologies have relatively high compressive strength, which can improve the permeability and operational stability of the separator during battery production and normal operation, thereby enhancing the battery's electrochemical performance. Furthermore, these polymer particles can increase the melting rate to accelerate the closure of the base membrane's pores. Therefore, polymer particles with this morphology can further reduce the risk of thermal runaway in batteries and improve battery safety.
[0116] In some embodiments, the volume distribution particle size D of the polymer particles contained in the coating is v 50 can be 0.1 μm to 5 μm, optionally 0.3 μm to 3 μm, and in the exemplary embodiment, can be 0.1 μm, 0.5 μm, 1 μm, 1.5 μm, 2 μm, 2.5 μm, 3 μm, 3.5 μm, 4 μm, 4.5 μm, 5 μm and other typical but non-limiting particle sizes. By controlling the particle size of the polymer particles, if controlled within this range, the uniformity of the distribution of the polymer particles in the coating and the mechanical properties such as compressive strength can be improved, the air permeability and stability of the diaphragm can be improved, and the hot melt response rate of the coating, i.e., the diaphragm, can also be improved. Wherein, unless otherwise specified, in the embodiments of the present application, the volume distribution particle size D of the polymer particles and the inorganic particles below is v 50 is determined by a particle size analyzer-laser diffraction method. Specifically, the standard GB / T 19077-2016 can be referred to, and the measurement is performed using a laser diffraction scattering particle size analyzer (Mastersizer 3000 laser particle size analyzer) according to the manufacturer's instructions.
[0117] In some embodiments, the polymer of the polymer particles in the above embodiments contains non-ionic groups. In the exemplary embodiments, the non-ionic groups may include at least one of ethoxy, hydroxyl, and carboxylate groups. The material of the polymer particles contains non-ionic groups, specifically such types of non-ionic groups, which can further enhance the above-mentioned effects of the polymer particles, in particular, enhance the compressive properties of the polymer particles, thereby enhancing the compressive resistance and stability of the diaphragm during the battery production process and normal operation; it can also enhance the uniformity of the dispersion of the polymer particles in the coating, thereby enhancing the air permeability and stability of the diaphragm. It can also adjust the melting point range of the polymer particles and enhance their hot melt response rate. In addition, the non-ionic group can be a grafted side chain of the polymer or connected to the main chain of the polymer.
[0118] In some embodiments, the polymer of the polymer particles in each of the above embodiments may include at least one of polystyrene, polyolefin, polyimide, melamine resin, phenol resin, cellulose, polyester, polyphenylene sulfide, polyaramid, polyamide-imide, copolymers of butyl acrylate and ethyl methacrylate, and their respective modified polymers. By selecting the polymer material of the polymer particles, such as these polymers, based on the above-mentioned branched carbon number range or further molecular weight of 1500 to 5000 and PDI of 3 to 11, the mechanical properties of the polymer particles, such as compressive strength, can be effectively improved to further improve the air permeability and working stability of the diaphragm and adjust its hot melt response rate, thereby enhancing the volatilization effect of the diaphragm of the present application embodiment.
[0119] In addition, the polymer particles in the above embodiments can be solid particles, and of course they can also be hollow particles. In the embodiments of the present application, solid particles have relatively high compressive resistance compared to hollow particles, thereby improving the mechanical properties and stability of the separator during battery production and normal operation, such as compressive resistance. For example, the polymer particles will not be deformed due to the extrusion force during battery production or use, thereby preventing the base membrane from blocking pores. Therefore, in the embodiments of the present application, solid polymer particles are relatively preferred compared to hollow polymer particles.
[0120] The melting points of the polymer particles in the above examples were measured to be between 100 and 110°C.
[0121] In some embodiments, based on the total weight (dry weight) of the coating layer in the separators of the above embodiments being 100%, the content of the polymer particles in the coating layer can be ≥22 wt%, and further can be 22 wt% to 37 wt%. By controlling and adjusting the content of the polymer particles in the coating layer within this range, the mechanical properties of the coating layer, such as compressive strength, can be improved, thereby enhancing the permeability and stability of the separator. Furthermore, when the battery stability is abnormal, the molten polymer can be enhanced to melt and seal the pores in the base film, thereby improving the barrier properties of the separator during thermal runaway.
[0122] In some embodiments, the coatings included in the separators of the aforementioned embodiments further contain inorganic particulate fillers. Adding the inorganic particulate fillers to the coatings can, on the one hand, improve the coating's mechanical properties, such as compressive strength, and enhance the permeability and stability of the separator during battery production and normal operation. Furthermore, they can synergize with the aforementioned polymer particles, improving the separator's permeability, liquid storage capacity, and mechanical properties such as thermal shrinkage resistance, while also enhancing the separator's responsiveness to hot melt. Furthermore, the inorganic particulate fillers ideally form a mixture with the aforementioned polymer particles in the coating.
[0123] In an embodiment, the content of the inorganic particle filler in the coating can be 18 wt % to 22 wt % based on the total weight (dry weight) of the coating as 100%. By controlling the content ratio of the inorganic particle filler and the polymer particles in the coating, the synergistic effect between the two can be enhanced, while fully evaporating the respective effects described above. This can further improve the permeability and mechanical properties of the separator, and further enhance the electrochemical performance and safety performance of the battery, such as the capacity retention rate.
[0124] In the embodiment, the average particle size D of the inorganic particle filler is v 50 is 1 μm to 1.5 μm. By adjusting the inorganic particle filler, it is compounded with the polymer particle size, such as controlling the D v The inorganic filler particles in the 1μm to 1.5μm range act as a coating framework, improving the coating's mechanical properties, such as compressive strength. They also work together with the organic particles in the aforementioned particle size range to enhance the separator's air permeability. Testing has shown that the separator's air permeability and stability can reach the levels shown in Table 1 below. Furthermore, during thermal melting, the inorganic filler particles in this particle size range fully function as a framework, allowing the polymer particles to melt and seal the base membrane's pores. They also work together with the base membrane to isolate the positive and negative electrodes, reducing the risk of short-circuit thermal runaway.
[0125] In an embodiment, the inorganic particle filler may include at least one of inorganic particles having a dielectric constant of 5 or greater, inorganic particles having ion conductivity but not storing ions, and inorganic particles capable of undergoing electrochemical reactions.
[0126] In an exemplary embodiment, the inorganic material of the inorganic particles having a dielectric constant of 5 or more includes boehmite, aluminum oxide, zinc oxide, silicon oxide, titanium oxide, zirconium oxide, barium oxide, calcium oxide, magnesium oxide, nickel oxide, tin oxide, cerium oxide, yttrium oxide, hafnium oxide, aluminum hydroxide, magnesium hydroxide, silicon carbide, boron carbide, aluminum nitride, silicon nitride, boron nitride, magnesium fluoride, calcium fluoride, barium fluoride, barium sulfate, magnesium aluminum silicate, lithium magnesium silicate, sodium magnesium silicate, bentonite, hectorite, zirconium titanate, barium titanate, Pb(Zr,Ti)O3, Pb 1-m Lam Zr 1-n TinO3、Pb(Mg3Nb 2 / 3 )O3-PbTiO3, and at least one of their respective modified inorganic particles, 0<m<1, 0<n<1.
[0127] In an exemplary embodiment, the inorganic material of the inorganic particles having ion conductivity but not storing ions includes Li3PO4, lithium titanium phosphate Li x1 Ti y1 (PO4)3, lithium aluminum titanium phosphate Li x2 Al y2 Ti z1 (PO4)3, (LiAlTiP) x3 O y3 Type glass, lanthanum lithium titanate Li x4 La y4 TiO3, lithium germanium thiophosphate Li x5 Ge y5 P z2 S w , lithium nitride Li x6 N y6 、SiS2 type glass Li x7 Si y7 S z3 and P2S5 glass Li x8 P y8 S z4 At least one of , 0<x1<2, 0<y1<3, 0<x2<2, 0<y2<1, 0<z1<3, 0<x3<4, 0<y3<13, 0<x4<2, 0<y4<3, 0<x5<4, 0<y5<1, 0<z2<1, 0<w<5, 0<x6<4, 0<y6<2, 0<x7<3, 0<y7<2, 0<z3<4, 0<x8<3, 0<y8<3, 0<z4<7;
[0128] In an exemplary embodiment, the inorganic material of the electrochemically reactive inorganic particles includes at least one of lithium-containing transition metal oxides, lithium-containing phosphates, carbon-based materials, silicon-based materials, tin-based materials, and lithium-titanium compounds.
[0129] By carefully selecting the type of inorganic particle filler material, the aforementioned effects of the inorganic particle filler are enhanced, further improving the synergistic effect between the inorganic particle filler and the polymer particles, thereby improving the mechanical properties and stability of the coating layer, i.e., the separator, and enhancing the electrochemical properties and safety performance of the battery, such as the capacity retention rate. In particular, the inorganic particle fillers of some of the aforementioned inorganic materials also have good liquid absorption and storage capabilities, thereby improving the liquid absorption and storage capabilities of the separator.
[0130] Based on the polymer particles and inorganic particulate fillers described above, in this exemplary embodiment, the polymer particles contained in the coating are low-density polyethylene, specifically low-density polyethylene particles, and further, low-density polyethylene containing non-ionic groups. The low-density polyethylene refers to high-pressure polyethylene (LDPE), specifically polyethylene with a molecular weight of less than 10,000.
[0131] The above-mentioned inorganic particles are compounded with the low-density polyethylene particles to enhance the above-mentioned synergistic effect between the polymer particles and the inorganic particle fillers, thereby improving the mechanical properties and working stability of the coating of the embodiment of the present application, that is, the diaphragm, and also improving the liquid storage capacity of the diaphragm.
[0132] In some embodiments, the coating contained in the diaphragm of each of the above embodiments further contains a solidified aqueous binder. By adding an aqueous binder to the coating, the bonding force between the polymer particles or the inorganic particle filler can be effectively enhanced, thereby improving the mechanical properties of the coating such as compressive strength, and enhancing the bonding force between the coating and the base film. At the same time, the aqueous binder can also play a synergistic role with the polymer particles or further with the inorganic particle filler, adjusting the permeability and working stability of the coating, that is, the diaphragm, and improving the thermal responsiveness of the polymer particles to seal the pores of the base film, thereby improving the electrochemical performance and safety performance of the battery, such as the capacity retention rate.
[0133] In an embodiment, the content of the aqueous binder in the coating can be 18 wt % to 27 wt % based on the total weight (dry weight) of the coating as 100%. By controlling the content of the aqueous binder in the coating, the mechanical properties of the coating and the adhesion between the coating and the base film can be further enhanced, thereby further adjusting the air permeability and operational stability of the coating, i.e., the diaphragm.
[0134] In the embodiments, the thermal decomposition temperature of the cured aqueous binder is higher than 160°C, and can be selected from 160°C to 300°C. By selecting the decomposition temperature characteristic of the aqueous binder, the mechanical properties of the coating and the adhesion between the coating and the base film are enhanced, and the compressive resistance and air permeability of the separator, as well as its operational stability, are improved. This enhances the separator's barrier function in the event of abnormal battery thermal conditions, reducing the risk of thermal runaway.
[0135] In an embodiment, the aqueous binder may be a water-soluble binder or an emulsion binder. In an exemplary embodiment, the aqueous binder may include at least one of polyvinyl alcohol, polyacrylic acid-polyacrylonitrile copolymer, polyacrylate-polyacrylonitrile copolymer, polyether acrylate, polyurethane, polyacrylate, polycarbonate, polyethylene oxide, rubber, polyacrylic acid, polyacrylonitrile, gelatin, chitosan, sodium alginate, cyanoacrylate, polymerized cyclic ether derivatives, and hydroxyl derivatives of cyclodextrin. These aqueous binders can enhance the bonding force between polymer particles or further inorganic particle fillers, thereby improving the mechanical properties of the coating and enhancing the bonding force between the coating and the base film. The mechanical properties such as compressive strength and the working stability of the diaphragm are further adjusted to improve the electrochemical properties and safety performance of the battery, including capacity retention rate.
[0136] In an embodiment, when the coating contains both the above-mentioned inorganic particle filler and the aqueous binder, the dry weight ratio of the above-mentioned polymer particles, inorganic particle filler, and aqueous binder in the coating can be (22 to 37): (18 to 22): (18 to 27). By controlling the content ratio of the three components in the coating, the above-mentioned effects of each component and the synergistic effect between the three components are further enhanced, thereby further improving the mechanical properties of the separator, such as compressive strength, and improving the electrochemical properties and safety performance of the battery, such as the capacity retention rate.
[0137] Based on the coating schemes in the above embodiments, in some embodiments, the coating thickness can be 2μm to 5μm. In exemplary embodiments, the coating thickness can be 2μm, 3μm, 4μm, 5μm, and other typical but non-limiting thicknesses. By controlling the coating thickness, it is possible to control the content of components such as polymer particles, thereby adjusting and improving the polymer particles' ability to play the role described above, thereby improving the efficiency of melting and effectively sealing the pores of the base membrane during battery thermal anomalies, reducing or preventing the risk of thermal runaway, and simultaneously improving the mechanical properties such as compressive strength and operational stability of the coating, i.e., the separator, thereby improving the battery's electrochemical performance and safety performance, such as capacity retention.
[0138] Furthermore, the coating included in the separators of the above embodiments can be disposed on one surface of the base membrane, or alternatively, on two opposing surfaces of the base membrane. Based on considerations such as battery energy density and dendrite formation characteristics, in the embodiments, the coating is disposed on one surface of the base membrane, meaning that the coating is not disposed on the opposing surface of the base membrane.
[0139] The base film contained in the separators of the above embodiments can be a battery organic separator. For example, in the embodiments, the conductive thickness of the base film can be 4μm to 7μm. In other embodiments, the air permeability of the base film can be 180s / 100cc to 240s / 100cc. In the exemplary embodiment, the material of the base film includes at least one of non-woven fabrics, polyolefins, polyethylene terephthalate, polybutylene terephthalate, polyester, polyacetal, polyamide, polycarbonate, polyimide, polyetheretherketone, polyethersulfone, polyphenylene ether, polyphenylene sulfide, and polyethylene naphthalene. The base films with these characteristics and materials can be combined with the above coating and play a synergistic role on the basis of giving full play to the role of the battery separator, so that the separator has high mechanical properties such as compressive strength, good air permeability, and improves the electrochemical properties and safety performance of the battery such as capacity retention rate.
[0140] In some embodiments, the above-mentioned base membrane can also be a modified base membrane, such as a base membrane modified with at least one modifier such as flame retardants, fiber-like substances, electrochemically inert ceramics, etc., to improve the thermal stability of the base membrane, to cooperate with the above-mentioned coating, and further improve the mechanical properties and safety performance of the diaphragm of the embodiment of the present application.
[0141] Method for preparing diaphragm
[0142] In a second aspect, the present invention provides a method for preparing a diaphragm. The process flow of the method for preparing a diaphragm according to the present invention is shown in FIG1 . The method for preparing a diaphragm according to the present invention may include the following steps:
[0143] S01: providing a basement membrane;
[0144] S02: providing coating slurry;
[0145] S03: coating the coating slurry on at least one surface of the base film, performing a drying process to form a coating layer, and obtaining a separator.
[0146] In the method for preparing the separator according to the embodiment of the present application, a coating is formed on the surface of the base film after the coating slurry is applied. The coating is then bonded to the surface of the base film. Since the method for preparing the separator according to the embodiment of the present application is intended to prepare the separator according to the embodiment of the present application, the formed coating contains polymer particles, and the number of carbon atoms in the branched chains of the polymer particles is 1 to 10.
[0147] The diaphragm preparation method of the embodiment of the present application directly forms a film of a slurry of polymer particles having a branched carbon number of 1 to 10 on a base film, so that the prepared diaphragm is combined with a coating on at least one surface to achieve the coating's modification effect on the base film. The coating is then the coating contained in the diaphragm of the above text application embodiment. Therefore, the diaphragm prepared by the diaphragm preparation method of the embodiment of the present application has the mechanical properties such as compressive strength and working stability and hot melt responsiveness as the diaphragm of the above text application embodiment, and can also effectively further reduce the risk of thermal runaway of the battery and improve the electrochemical properties and safety performance of the battery, such as the capacity retention rate. In addition, the process parameters of the diaphragm preparation method of the embodiment of the present application are controllable, and the quality and electrochemical properties of the prepared diaphragm are stable.
[0148] Step S01:
[0149] The base film in step S01 can be the base film contained in the separator of the embodiment of the above-mentioned application. Therefore, the base film can be the base film contained in the separator of the embodiment of the above-mentioned application. As in the embodiment, the thickness of the provided base film can be 4μm to 7μm, and its air permeability can be 180s / 100cc to 240s / 100cc. Its material can include at least one of non-woven fabric, polyolefin, polyethylene terephthalate, polybutylene terephthalate, polyester, polyacetal, polyamide, polycarbonate, polyimide, polyetheretherketone, polyethersulfone, polyphenylene oxide, polyphenylene sulfide, and polyethylene naphthalene.
[0150] Step S02:
[0151] Since the coating slurry in step S02 is the slurry that forms the coating contained in the diaphragm of the above text application embodiment, the slurry must contain polymer particles and solvents. In the embodiment, it may further contain inorganic particle fillers and aqueous binders. Therefore, the material types and content ratios of the polymer particles contained in the coating slurry, or the inorganic particle fillers and aqueous binders further contained therein, are the same as the types and content ratios of the polymer particles, inorganic particle fillers and aqueous binders contained in the coating of the diaphragm of the above text application embodiment, such as the number of carbon atoms in the side chains of the polymer is 1 to 10, optionally 1 to 5; further, the weight-average molecular weight of the polymer particles is 1500 to 5000, and the polydispersity index PDI is 3 to 11. Therefore, in order to save space, the types, content ratios, etc. of polymer particles, inorganic particle fillers and aqueous binders will not be described in detail here.
[0152] In order to improve the film-forming quality of the coating slurry, improve the quality of the coating as well as the air permeability, pressure resistance and other properties, in one embodiment, the solid content of the coating slurry can be 30wt% to 40wt%; in other embodiments, the viscosity of the coating slurry at 25°C is 500mPa·s to 800mPa·s.
[0153] In some embodiments, when the coating slurry in step S02 is formed by mixing polymer particles, inorganic particle fillers and aqueous binders in a solvent; then the mass ratio of polymer particles, inorganic particle fillers, aqueous binders and water in the coating slurry can be (22 to 37): (18 to 22): (18 to 27): (22 to 32). This ratio refers to the mixing ratio of aqueous binder to polymer particles and inorganic particle fillers before curing. By adjusting the ratio of the three, the film-forming quality of the coating slurry is improved, and the compressive resistance and other properties of the formed coating are enhanced, thereby further improving the electrochemical performance of the battery and reducing the risk of thermal runaway of the battery.
[0154] The aqueous binder may be a pre-cured aqueous binder, such as the aqueous binder described above. In an exemplary embodiment, the aqueous binder may be a pre-cured aqueous binder comprising at least one of polyvinyl alcohol, polyacrylic acid-polyacrylonitrile copolymer, polyacrylate-polyacrylonitrile copolymer, polyether acrylate, polyurethane, polyacrylate, polycarbonate, polyethylene oxide, rubber, polyacrylic acid, polyacrylonitrile, gelatin, chitosan, sodium alginate, cyanoacrylate, polymerized cyclic ether derivatives, and hydroxyl derivatives of cyclodextrin.
[0155] For example, in the embodiments, the aqueous binder is added as an aqueous binder solution to effectively adjust the viscosity of the coating slurry, improve the dispersion uniformity and stability of the coating slurry components, and improve the film-forming quality of the coating slurry. When the aqueous binder is added as an aqueous binder solution, in the embodiments, the viscosity of the aqueous binder solution at 25°C can be 3000mPa·s to 10000mPa·s; in other embodiments, the solid content of the aqueous binder solution is 40wt% to 50wt%. By controlling and adjusting the viscosity of the aqueous binder solution or the solid content at the same time, the positive effect of the aqueous binder on the coating slurry can be further enhanced, further improving the slurry stability and dispersibility.
[0156] In the embodiment, when the polymer particles contained in the coating slurry are polymer particles containing nonionic groups, the polymer particles can be prepared according to a method comprising the following steps:
[0157] Step S021: mixing and reacting polymer precursor particles, an ethoxy-containing polymer, and an initiator to obtain polymer particles containing nonionic groups;
[0158] Step S022: emulsifying the polymer particles containing nonionic groups with a nonionic surfactant to obtain a nonionic polymer emulsion.
[0159] During the reaction process of step S021 , the polymer precursor particles and the ethoxy-containing polymer undergo a polymerization reaction under the action of an initiator, so that the ethoxy-containing group is grafted onto the polymer particles.
[0160] In the embodiment, the polymer precursor particles, the ethoxy-containing polymer and the initiator are mixed in a mass ratio of (300 to 400): (90 to 125): (20 to 50).
[0161] In an embodiment, the reaction temperature in step S021 can be 130° C. to 140° C., and the reaction time should be sufficient, such as 2.5 to 4 hours at 130° C. to 140° C. At the same time, during the reaction process, the molten reactants are stirred to improve the efficiency and uniformity of the reaction.
[0162] By controlling and adjusting the mixing ratio of the reactants in step S021, or further controlling the reaction conditions, on the basis of improving the polymer reaction efficiency, the number of branched carbon atoms in the polymer particles is increased from 1 to 10, further to 1-5, and at the same time, the content of grafted non-ionic groups such as ethoxy groups can be increased, thereby further improving the non-ionic group modification effect of the polymer particles, thereby further improving the above effects of the polymer particles, especially improving the mechanical properties of the polymer particles such as compressive strength.
[0163] In an exemplary embodiment, the material of the polymer precursor particles may include at least one of polystyrene, polyolefin, polyimide, melamine resin, phenol resin, cellulose, polyester, polyphenylene sulfide, polyaramid, polyamideimide, and a copolymer of butyl acrylate and ethyl methacrylate.
[0164] The ethoxy-containing polymer may include at least one of allyl polyethylene glycol and bisallyl polyether.
[0165] The initiator may include at least one of di-tert-butyl peroxide and dicumyl peroxide.
[0166] The polymer precursor particles, ethoxylated polymer, and initiator can undergo a polymerization reaction in step S021 to improve the efficiency of graft modification. The ethoxylated polymer can effectively provide ethoxylated nonionic groups to achieve graft modification of the ethoxylated nonionic groups of the polymer precursor particles.
[0167] In step S022, during the emulsification process, a nonionic surfactant and nonionic group-containing polymer particles are formed into an emulsion in a solvent. In an embodiment, the mass ratio of the nonionic group-containing polymer particles to the nonionic surfactant can be (4 to 6):1 for the emulsification process. The solvent can be water.
[0168] In addition, the mixing ratio of the nonionic surfactant and the polymer particles containing nonionic groups, as well as the amount of added aqueous solvent, can be controlled to adjust and control the relevant properties of the nonionic polymer emulsion, such as viscosity, solid content, pH value, etc., thereby improving the dispersion uniformity and stability of the polymer particles in the coating slurry, thereby improving the above-mentioned effect of forming the coating and improving the electrochemical performance and safety performance of the prepared separator. For example, by controlling and adjusting the conditions of the emulsification treatment in step S022, the nonionic polymer emulsion has at least one of the following properties:
[0169] (1) The viscosity of the nonionic polymer emulsion at 25° C. is 10 mPa·s to 100 mPa·s;
[0170] (2) the solid content of the nonionic polymer emulsion is 35 wt % to 40 wt %;
[0171] (3) The pH value of the nonionic polymer emulsion is 5 to 6;
[0172] In the embodiments, the above mixing ratio of the nonionic surfactant and the polymer particles can effectively adjust the viscosity and solid content of the nonionic polymer emulsion, thereby improving the dispersibility of the polymer particles and improving the uniformity and stability of the coating slurry.
[0173] In some embodiments, the nonionic surfactant may include a molecular structure of
[0174] Wherein, R1 is a carbon chain alkyl group. In an exemplary embodiment, when it is a carbon chain alkyl group, R1 is a long carbon chain alkyl group of C12 to C18.
[0175] R2 is a hydrophilic group. In an exemplary embodiment, R2 is at least one of a carboxyl group, an amine group, an aldehyde group, an alcohol group, an amino group, and an amide group.
[0176] n is a positive integer from 3 to 20. In the examples, n can be a typical but non-limiting positive integer such as 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20.
[0177] In an exemplary embodiment, the nonionic surfactant includes at least one of fatty alcohol polyoxyethylene ether, alkylphenol polyoxyethylene ether, fatty acid polyoxyethylene ester, castor oil polyoxyethylene ether, fatty amine polyoxyethylene ether, sorbitan fatty acid ester, and polyoxyethylene sorbitan fatty acid ester.
[0178] By selecting the type of nonionic surfactant, the stability of the nonionic polymer emulsion can be improved, its dispersibility in the coating slurry can be improved, and thus the dispersion uniformity and stability of the polymer particles can be improved.
[0179] In addition, there is no specific order between step S01 and step S02 above. The order can be adjusted according to actual production, or they can be performed simultaneously.
[0180] Step S03:
[0181] The coating slurry is applied to the base film in step S02 to form a wet film, i.e., the coating layer before drying. The coating method is not limited to any method capable of forming a film of the coating slurry on the base film, and is within the scope of the embodiments disclosed herein. Examples include, but are not limited to, brushing, roller coating, and spraying. Furthermore, the coating process conditions can be further adjusted to optimize the film quality, thickness, and air permeability.
[0182] In the embodiment, the coating slurry in step S02 may be applied at a rate of 20 m / min to 100 m / min, and further at a rate of 20 m / min to 50 m / min. In exemplary embodiments, the rate may be 20 m / min, 30 m / min, 40 m / min, 50 m / min, 60 m / min, 70 m / min, 80 m / min, 90 m / min, 100 m / min, and the like, which are typical but non-limiting rates. This coating rate can improve the quality of the coating and adjust the air permeability and thickness.
[0183] The drying process is primarily intended to remove the solvent from the wet film. Based on the melting temperature range of the organic particles contained in the coating slurry, the drying temperature should be below the melting temperature of the organic particles and should ensure the quality and stability of the coating. For example, in the embodiment, the drying temperature can be 50°C to 70°C. In exemplary embodiments, typical but non-limiting temperatures such as 50°C, 60°C, 61°C, 62°C, 63°C, 64°C, 65°C, 66°C, 67°C, 68°C, 69°C, and 70°C can be used. Within this drying temperature range, the drying time should be sufficient, such as a drying time of 1 to 5 minutes.
[0184] Battery
[0185] In a third aspect, an embodiment of the present application provides a battery comprising a positive electrode, a negative electrode, and a separator disposed between the positive electrode and the negative electrode, wherein the separator is the separator of the embodiment of the present application.
[0186] In the examples, the separator is coated only on one surface, with the coated surface facing the negative electrode. By orienting the coating toward the negative electrode, the separator can fully utilize the functions described in the examples above, further improving the battery's electrochemical performance, reducing the risk of thermal runaway, and enhancing battery safety. Furthermore, by only coating the separator on one surface, the overall thickness of the separator can be effectively reduced, thereby increasing the battery's energy density.
[0187] In some embodiments, the battery of the present application can be a secondary battery. When the battery of the present application is a secondary battery, it includes a positive electrode, a separator, and a negative electrode. Specifically, the negative electrode of the secondary battery is the negative electrode of the embodiment described above, and the negative electrode contains the modified artificial graphite of the embodiment described above.
[0188] In this way, the battery of the embodiment of the present application, specifically the secondary battery, has high energy density, high rate capability and good cycle stability.
[0189] In an embodiment, the secondary battery of the present application may include any one of a battery cell, a battery module, and a battery pack.
[0190] A battery cell is a structure that includes a battery housing and a cell encapsulated within the housing. The shape of a battery cell is not particularly limited and can be cylindrical, square, or any other shape. A square-shaped battery cell 10 is shown in FIG2 .
[0191] In some embodiments, as shown in Figure 3, the outer packaging of the battery cell 10 may include a shell 11 and a cover plate 13. The shell 11 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 11 has an opening connected to the receiving cavity, and the cover plate 13 is used to cover the opening to close the receiving cavity. The positive electrode, diaphragm and negative electrode contained in the secondary battery of the embodiment of the present application can be formed into an electrode assembly 12 through a winding process and / or a lamination process. The electrode assembly 12 is encapsulated in the receiving cavity. The electrolyte is infiltrated in the electrode assembly 12. The number of electrode assemblies 12 contained in the battery cell 10 can be one or more, which can be adjusted according to actual needs.
[0192] The preparation method of the battery cell 10 is well known. In some embodiments, the positive electrode, separator, negative electrode, and electrolyte can be assembled to form the battery cell 10. As an example, the positive electrode, separator, and negative electrode can be wound or laminated to form the electrode assembly 12. The electrode assembly 12 is placed in an outer package, dried, and then injected with electrolyte. The battery cell 10 is then vacuum packaged, allowed to stand, formed, and shaped.
[0193] A battery module is assembled from the battery cells 10 , that is, it may contain a plurality of battery cells 10 , and the specific number can be adjusted according to the application and capacity of the battery module.
[0194] In some embodiments, FIG4 is a schematic diagram of an exemplary battery module 20. As shown in FIG4 , in the battery module 20, multiple battery cells 10 may be arranged sequentially along the length of the battery module 20. Of course, any other arrangement is also possible. Furthermore, the multiple battery cells 10 may be secured together using fasteners.
[0195] Optionally, the battery module 20 may further include a housing having an accommodation space, and the plurality of battery cells 10 may be accommodated in the accommodation space.
[0196] A battery pack is assembled from the battery cells 10 described above, and may contain multiple battery cells 10, wherein multiple battery cells 10 may be assembled into the battery module 20 described above. The specific number of battery cells 10 or battery modules 20 contained in a battery pack may be adjusted according to the application and capacity of the battery pack.
[0197] In the embodiment, Figures 5 and 6 are schematic diagrams of an exemplary battery pack 30. The battery pack 30 may include a battery box and multiple battery modules 20 disposed within the battery box. The battery box includes an upper box body 31 and a lower box body 32. The upper box body 31 covers the lower box body 32 and forms an enclosed space for accommodating the battery modules 20. The multiple battery modules 20 may be arranged in any manner within the battery box.
[0198] Electrical devices
[0199] Fourthly, embodiments of the present application further provide an electrical device comprising the battery of the aforementioned embodiments, which may further comprise a secondary battery. The battery can serve as both a power source and an energy storage unit for the electrical device. Consequently, the electrical device of the embodiments of the present application has a long standby or battery life.
[0200] Electrical devices may include, but are not limited to, mobile devices (e.g., mobile phones, laptops, etc.), electric vehicles (e.g., pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships, satellites, energy storage systems, etc. These electrical devices may use secondary batteries, battery modules, or battery packs based on their usage requirements.
[0201] Figure 7 is a schematic diagram of an exemplary electric device. This device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. To meet the high power and high energy density requirements of this device, a battery pack or battery module may be used.
[0202] As another example, the electric device may be a mobile phone, a tablet computer, a laptop computer, etc. Such an electric device is usually required to be lightweight and thin, and may use a secondary battery as a power source.
[0203] Example
[0204] Below, the embodiment of the present application is described. The embodiment described below is exemplary and is only used to explain the present application, and is not to be construed as limiting the present application. Where specific techniques or conditions are not specified in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. Reagents or instruments used that do not specify the manufacturer are conventional products that can be obtained commercially.
[0205] 1. Diaphragm and its preparation method embodiment
[0206] Example A1
[0207] This embodiment provides a separator and a method for preparing the same. The separator comprises a PE base film and a coating bonded to one surface of the PE base film. The PE base film is 7 μm thick, and the coating is 3 μm thick. The coating contains nonionic linear low-density polyethylene particles containing ethoxy groups. Testing revealed that the polymer's molecular weight, PDI, and branch carbon number are shown in Table 1 below.
[0208] The diaphragm preparation method of this embodiment includes the following steps:
[0209] S1. Preparation of coating slurry:
[0210] S11. Preparation of polymer particles:
[0211] a. Mix linear low-density polyethylene (LLDPE): allyl polyethylene glycol: di-tert-butyl peroxide in a ratio of 350:100:50, heat and melt, stir evenly, and keep the temperature at 140°C for 3h to obtain an intermediate product;
[0212] b. Mix the intermediate product and nonionic emulsifier (fatty alcohol polyoxyethylene ether AEO-3) in a ratio of 4.5:1, heat and melt, stir until a uniform emulsion is formed, add water and adjust the pressure to an appropriate 50 mPa·s (25°C), and the solid content to 35% to obtain a modified LLDPE emulsion; wherein the polymer particles have a weight-average molecular weight of 1500, a PDI of 5, and a branched carbon number of 5 to 10;
[0213] S12. Prepare coating slurry:
[0214] Nonionic polyethylene wax emulsion, polymethyl methacrylate, boehmite, and water were mixed in a ratio of polymer particles: polymethyl methacrylate: boehmite: water = 25%: 19%: 26%: 30%. All materials were added to a double planetary stirring tank, and then stirred at 30 rpm and 2000 rpm for 3 hours, with vacuum defoaming throughout the process. The viscosity of the coating slurry was controlled at 700 mPa·s (25°C).
[0215] S2. Film formation treatment of coating slurry on the surface of base film:
[0216] The coating slurry in step S1 was coated on one side of a 7 μm PE base film to form a wet film, and then dried to form a 3 μm coating on one side of the PE base film; wherein the coating slurry coating speed was 60 m / min, the oven temperature was 60° C., and the total drying time was 5 min.
[0217] Example A2
[0218] This example provides a diaphragm and a method for preparing the same. The diaphragm in this example is identical to the diaphragm in Example A1, except for the modification conditions of the polymer particles contained in the coating. Specifically, in this example, LLDPE: allyl polyethylene glycol: di-tert-butyl peroxide (400:115:20) was mixed, heated, melted, and stirred until uniformly mixed. The mixture was then heated at 130°C for 3 hours to obtain an intermediate product. The resulting modified LLDPE emulsion had a weight-average molecular weight of 5000 (see Table 1), a PDI of 6, and 5 to 10 carbon atoms in the branches.
[0219] The diaphragm of this embodiment was prepared by referring to the diaphragm preparation method in Example A1.
[0220] Example A3
[0221] This example provides a diaphragm and a method for preparing the same. The diaphragm in this example is identical to the diaphragm in Example A1, except for the modification conditions of the polymer particles contained in the coating. Specifically, in this example, LLDPE: allyl polyethylene glycol: di-tert-butyl peroxide (300:125:40) was mixed, heated, melted, and stirred until uniformly mixed. The mixture was then heated at 140°C for 2.5 hours to obtain an intermediate product. The resulting modified LLDPE emulsion had a weight-average molecular weight of 1500 (see Table 1), a PDI of 11, and 5 to 10 carbon atoms in the branches.
[0222] Example A4
[0223] This example provides a diaphragm and a method for preparing the same. This example's diaphragm is identical to the diaphragm in Example A1, except for the modification conditions of the polymer particles in the coating. Specifically, LLDPE: allyl polyethylene glycol: di-tert-butyl peroxide (350:90:40) is mixed, heated, melted, and stirred until uniformly mixed. The mixture is then heated at 140°C for 4 hours to obtain an intermediate product. The resulting modified LLDPE emulsion has a weight-average molecular weight of 1500 (see Table 1), a PDI of 5, and 1 to 5 carbon atoms in its branches.
[0224] Example A5
[0225] This embodiment provides a diaphragm and a method for preparing the same. The diaphragm of this embodiment is identical to the diaphragm of Example A1, except for the polymer particles contained in the coating. Specifically, in this embodiment, modified polyester: allyl polyethylene glycol: di-tert-butyl peroxide = 400:115:20 are mixed, heated, melted, and stirred evenly, and then maintained at a constant temperature of 130°C for 2.5 hours to obtain an intermediate product. The resulting modified polyester has a weight-average molecular weight of 3000 as shown in Table 1, a PDI of 5, and a branched carbon number of 5 to 10.
[0226] Example A6
[0227] This embodiment provides a separator and a method for preparing the same. The separator in this embodiment is identical to the separator in Example A1, except for the polymer particles contained in the coating. Specifically, the polymer particles in this embodiment are made of ordinary LLDPE, eliminating the need for the S11 modification step and proceeding directly to the S12 coating slurry preparation.
[0228] Example A7
[0229] This embodiment provides a separator and a method for preparing the same. The separator in this embodiment is identical to the separator in Example A1, except that the coating does not contain inorganic particulate filler. The coating slurry components are mixed in a ratio of 51% polymer particles: 19% polymethyl methacrylate: 0% boehmite: 30% water.
[0230] Example A8
[0231] This example provides a separator and a method for preparing the same. This comparative separator is identical to the separator in Example A1, except for the molecular weight of the polymer particles in the coating. Specifically, modified LLDPE: allyl polyethylene glycol: di-tert-butyl peroxide (350:100:60) was mixed, heated, melted, and stirred until uniformly mixed. The mixture was then heated at 150°C for 3 hours to obtain an intermediate product. The resulting modified LLDPE emulsion had a weight-average molecular weight of 1200 (see Table 1), a PDI of 5, and 5 to 10 carbon atoms in its branches.
[0232] Example A9
[0233] The separator of this example is identical to the separator of Example A1, except for the polymer particles contained in the coating. Specifically, in this comparative example, LLDPE: allyl polyethylene glycol: di-tert-butyl peroxide (400:115:5) was mixed, heated, melted, and stirred until uniformly mixed. The mixture was then heated at 120°C for 3 hours to obtain an intermediate product. The resulting modified LLDPE emulsion had a weight-average molecular weight of 6000 (as shown in Table 1), a PDI of 5, and 5 to 10 carbon atoms in its branches.
[0234] Comparative Example A1
[0235] This comparative example provides a separator, which is different from the separator in Example A1 in that the separator coating does not contain polymer particles. The remaining features are identical.
[0236] The preparation method for the diaphragm in this comparative example was similar to that in Example A1. The difference from Example A1 was that the coating slurry was prepared by mixing the components of the coating slurry in a mass ratio of polymer particles: polymethyl methacrylate: boehmite: water = 0%: 19%: 51%: 30%. The steps and process conditions were the same.
[0237] Comparative Example A2
[0238] This comparative example provides a diaphragm. This diaphragm is identical to the diaphragm in Example A1, except for the polymer particles contained in the coating and the degree of branching. Specifically, low-density polyethylene (LDPE): allyl polyethylene glycol: di-tert-butyl peroxide (di-tert-butyl peroxide) was mixed in a ratio of 350:100:50, then heated, melted, and stirred until uniform. The mixture was then heated at 140°C for 3 hours to obtain an intermediate product. The resulting modified LDPE emulsion had a weight-average molecular weight of 1500 (see Table 1), a PDI of 5, and >11 carbon atoms in its branches.
[0239] 2. Secondary Battery Cell Example
[0240] Example B1 to Example B9 and Comparative Example B1 to Comparative Example B2;
[0241] Embodiments B1 to B9 and Comparative Examples B1 to B2 each provide a secondary battery cell, each comprising a positive electrode, a separator, and a negative electrode, and an electrolyte. The separators provided in Embodiments A1 to A9 and Comparative Examples A1 to A2 are the separators of secondary battery Embodiments B1 to B9 and Comparative Examples B1 to B2, respectively. The separator in Embodiment A1 serves as the separator in the battery cell of Secondary Battery Embodiment B1, the separator in Embodiment A2 serves as the separator in the battery cell of Secondary Battery Embodiment B2, and so on. The separator in Comparative Example A2 serves as the separator in the battery cell of Comparative Example B2.
[0242] The positive electrode was prepared as follows:
[0243] Using methyl pyrrolidone (NMP) as solvent, LiNi 0.8 Co 0.1 Mn 0.1 O2, carbon nanotubes (CNT), and binder (PVDF) are mixed in a mass ratio of 97:2:1 to prepare a positive electrode slurry with a solid content of 80%. The positive electrode slurry is evenly coated on aluminum foil and double-sided coating is performed. The surface density of each single side is 0.131g / 1540.25mm 2 After being fully dried, cold pressed and cut, the positive electrode sheet is obtained as the positive electrode.
[0244] Negative electrode: Using water as solvent, artificial graphite, conductive agent SP, dispersant (CMC), and binder (SBR) are mixed in a mass ratio of 96:1:1:2 to prepare a negative electrode slurry with a solid content of 58%. The positive electrode slurry is evenly coated on aluminum foil and double-sided coating is performed, where the surface density of each single side is 0.065g / 1540.25mm 2 After being fully dried, cold pressed and cut, the negative electrode sheet is obtained as the negative electrode.
[0245] Electrolyte: Ethylene carbonate (EC) and diethyl carbonate (DEC) were mixed at a volume ratio of 1:1 at room temperature, and LiPF6 was added to the mixed solution to obtain a solution with a concentration of 1 mol / L as the electrolyte.
[0246] Secondary battery assembly: In a low-humidity constant temperature room, the positive and negative electrode sheets prepared as above are stacked and wound in the order of "positive electrode-separator-negative electrode" to form a bare cell, which is then filled with electrolyte to assemble into a lithium-ion secondary battery.
[0247] Performance tests of diaphragms and secondary battery cells
[0248] The separators and secondary battery cells provided in the above embodiments and comparative examples were tested respectively.
[0249] 1. Diaphragm performance test:
[0250] 1.1 The membranes in Examples A1 to A9 and Comparative Examples A1 to A2 were tested for the properties listed in Table 1. All test methods were in accordance with national standards (if no national standards were available, industry standard methods were used). For example, molecular weight and PDI were measured using gel permeability chromatography (GPC) in accordance with GBT 27843-2011, "Test Method for Low Molecular Weight Component Content of Polymers in Chemicals." Air permeability was measured using a membrane air permeability tester in accordance with GB / T 36363-2018. The characterization method for branched carbon number is as follows:
[0251] use 13 C NMR test was performed using a Bruker AVANCE III 400 MHz NMR spectrometer with a resolution of 0.09 Hz. Deuterated o-dichlorobenzene was used as the solvent. 250 mg of the polymer sample was placed in 2.5 ml of the deuterated reagent and melted in a 130°C oil bath to form a homogeneous solution. 13 The C NMR test conditions were: 125°C, 20 Hz rotation speed, 90° pulse, Waltz16 continuous decoupling, spectral width 80 ppm, sampling time AQ 5 s, and delay time D1 10 s.
[0252] The measured results are shown in Table 1 below.
[0253] Table 1
[0254]
[0255] The membrane performance data in Table 1 show that the membranes in Examples A1 to A9 can seal the base membrane pores after heating at 120°C for 15 minutes, thereby improving battery safety. While Example A8, due to its relatively low molecular weight, exhibits a rapid melt response, with pores essentially completely closed after heating at 120°C for 15 minutes, its relatively low molecular weight results in relatively weak membrane stability during charge and discharge, as evidenced by relatively poor cycling performance. When using standard LLDPE, as in Example A6, the membrane stability is relatively weak, as evidenced by relatively poor cycling performance. Example A9, due to its relatively high molecular weight, exhibits a slow melt response, and while some air permeability is maintained after heating at 120°C for 15 minutes, indicating that the base membrane pores are not completely sealed, the air permeability is significantly reduced, for example, to 700 s / 100 cc. Compared to Comparative Example A2, the membranes in this embodiment exhibit higher thermal stability. For example, after injection aging and 1000 cycles, the air permeability of the membranes in this embodiment is significantly higher than that of Comparative Example A2.
[0256] The room-temperature air permeability of the separators in Examples A1 to A6 and A8 to A9 was comparable to that of Comparative Example A1, indicating that these organic particles did not affect the membrane's air permeability at room temperature. However, the room-temperature air permeability of Example A7 was poor, indicating that the addition of inorganic particulate fillers is preferred, as it can increase the coating's porosity and improve air permeability.
[0257] Therefore, by adjusting the number of branched carbon atoms in the polymer particles contained in the coating of the diaphragm of the embodiment of the present application to 1 to 10, or further controlling the polymer molecular weight to be in the range of 1500 to 5000 and the PDI to be 3 to 11, the mechanical properties such as compressive strength of the coating of the embodiment of the present application can be further improved, thereby ensuring the high mechanical properties such as compressive strength of the diaphragm during battery production and normal operation, thereby further improving the gas permeability and stability of the diaphragm, and thus significantly improving the electrochemical performance of the battery. On this basis, the overheating responsiveness of the polymer particles can be improved. When the battery temperature rises to the melting point of the polymer particles, they can effectively melt and seal the pores of the base membrane, causing the diaphragm to lose its gas permeability, thereby effectively terminating the metal ion migration or positive and negative electrode crosstalk reactions in the battery, thereby improving the battery safety performance.
[0258] 2. Secondary battery cell performance test:
[0259] 2.1 Secondary battery cell membrane air permeability test after liquid injection
[0260] After the secondary battery cells in the above-mentioned Examples B1 to B9 and Comparative Examples B1 to B2 were injected and formed under the same injection and formation conditions, the batteries were disassembled to obtain each diaphragm, and the air permeability of each diaphragm was tested according to the diaphragm permeability method in Section 1.1 above. The measured results are shown in "After injection and aging" in Table 1.
[0261] 2.2 Secondary battery cell membrane air permeability test after cycling
[0262] After the secondary battery cells in the above-mentioned Examples B1 to B9 and Comparative Examples B1 to B2 were cycled at 25°C and 1C / 1C conditions, the batteries were disassembled to obtain each diaphragm, and the air permeability of each diaphragm was tested according to the diaphragm permeability method in Section 1.1 above. The measured results are shown in "After 1000 cycles" in Table 1.
[0263] According to the relevant data in Table 1, the air permeability of the diaphragms after liquid injection and circulation in Examples A1 to A5 is comparable to that of Comparative Example A1. It can be seen that the optimization of modification (Comparative Example A6), molecular weight (Example A8) and degree of branching (Comparative Example A2) can effectively improve the pressure resistance of the polymer particles, thereby preventing the polymer particles from being squeezed and deformed by the battery expansion force during normal use of the diaphragm, thereby blocking the pores of the diaphragm and affecting the air permeability.
[0264] 2.3 Secondary battery cell cycle test
[0265] The secondary battery cells in the above-mentioned Examples B1 to B9 and Comparative Examples B1 to B2 were subjected to cycle tests at 25° C. and 1C / 1C conditions, and the test results are shown in Table 2.
[0266] Table 2
[0267] Example First cycle discharge capacity (%) Capacity retention rate after 100 cycles (%) Example B1 10089 Example B2 10089 Example B3 10089 Example B4 10090 Example B5 10089 Example B6 9580 Example B7 9888 Example B8 9785 Example B9 10090 Comparative Example B1 10090 Comparative Example B2 9576
[0268] Table 2 shows that the secondary battery cells of the present invention, due to the presence of the separators of the present invention, have coatings with high mechanical properties such as compressive strength. This effectively maintains the separator's good air permeability and structural stability during battery formation. For example, the capacity retention rates of Examples B1 to B5 after 1000 cycles are comparable to those of Comparative Example A1. This indicates that optimizing the modification (Comparative Example B6), molecular weight (Examples B8 and B9), and degree of branching (Comparative Example B2) can effectively enhance the pressure resistance of the polymer particles, preventing them from being squeezed and deformed by the expansion forces of battery cycling, which could clog the separator pores and affect cycling performance.
[0269] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit them. Although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some or all of the technical features therein. These modifications or replacements do not deviate the essence of the corresponding technical solutions from the scope of the technical solutions of the embodiments of the present application, and they should all be included in the scope of the claims and specification of the present application. In particular, as long as there is no structural conflict, the various technical features mentioned in the various embodiments can be combined in any way. The present application is not limited to the specific embodiments disclosed herein, but includes all technical solutions that fall within the scope of the claims.
Claims
1. A diaphragm, characterized in that: The invention comprises a base film and a coating layer arranged on at least one surface of the base film, wherein the coating layer contains polymer particles, and the number of carbon atoms in the branched chain of the polymer contained in the polymer particles is 1 to 10.
2. The diaphragm according to claim 1, characterized in that The polymer satisfies at least any one of the following conditions (1) to (3): (1) The weight average molecular weight of the polymer is 1500 to 5000, and can be 1500 to 2500; (2) the polydispersity index (PDI) of the polymer is 3 to 11, and can be 3 to 6; (3) The polymer has 1 to 5 carbon atoms in its branched chain.
3. The diaphragm according to claim 1 or 2, characterized in that: The polymer particles contain nonionic groups. Optionally, the nonionic groups include at least one of ethoxy groups, hydroxyl groups, and carboxylate groups.
4. The diaphragm according to any one of claims 1 to 3, characterized in that: Based on the total dry weight of the coating as 100%, the content of the polymer particles in the coating is ≥22wt%, and can be optionally 22wt% to 37wt%.
5. The diaphragm according to any one of claims 1 to 4, characterized in that: The polymer particles satisfy at least one of the following conditions (1) to (4): (1) Volume distribution particle size D of the polymer particles v 50: 0.1 μm to 5 μm; (2) The melting point of the polymer particles is 100°C to 110°C; (3) The polymer particles are in at least one of the following shapes: chain, spherical, quasi-spherical, fibrous, tubular, rod-shaped, amorphous, and pyramidal; (4) The polymer includes at least one of polystyrene, polyethylene, polyimide, melamine resin, phenol resin, cellulose, cellulose modifier, polypropylene, polyester, polyphenylene sulfide, polyaramid, polyamideimide, polyimide, and a copolymer of butyl acrylate and ethyl methacrylate.
6. The diaphragm according to any one of claims 1 to 5, characterized in that: The coating also includes an inorganic particulate filler.
7. The diaphragm according to claim 6, characterized in that Based on the total weight of the coating as 100%, the content of the inorganic particle filler in the coating is 18wt% to 22wt%; and / or The volume distribution particle size D of the inorganic particle filler v 50 is 1 μm to 1.5 μm; and / or The inorganic particle filler includes at least one of inorganic particles having a dielectric constant of 5 or more, inorganic particles having ion conductivity but not storing ions, and inorganic particles capable of electrochemical reaction.
8. The diaphragm according to any one of claims 1 to 7, characterized in that: The coating also includes an aqueous binder.
9. The diaphragm according to claim 8, characterized in that The aqueous binder satisfies at least one of the following conditions: The dry weight content of the aqueous binder in the coating is 18wt% to 27wt%; and / or The thermal decomposition temperature of the aqueous binder is ≥160°C.
10. The diaphragm according to any one of claims 1 to 9, characterized in that: The thickness of the base film is 4 μm to 7 μm; and / or The coating has a thickness of 2 μm to 5 μm; and / or The air permeability of the separator is 180s / 100cc to 240s / 100cc.
11. A method for preparing a diaphragm, characterized in that: The steps include: Providing a base film and a coating slurry containing polymer particles; the polymer particles contain a polymer having a branched carbon number of 1 to 10; The coating slurry is coated on at least one surface of the base film, and a coating is formed after drying to obtain a separator.
12. The preparation method according to claim 11, characterized in that: The coating slurry further comprises an inorganic particle filler and an aqueous binder; wherein the mass ratio of the polymer particles, the inorganic particle filler and the aqueous binder in the coating slurry is (22 to 37): (18 to 22): (18 to 27); and / or The solid content of the coating slurry is 30wt% to 40wt%; and / or The coating slurry has a viscosity of 100 to 1000 mPa·s at 25° C.
13. The preparation method according to claim 11 or 12, characterized in that: The polymer particles are prepared by a method comprising the following steps: The polymer precursor particles, the ethoxy-containing polymer and the initiator are mixed and reacted to obtain polymer particles containing nonionic groups; The polymer particles containing nonionic groups are emulsified with a nonionic surfactant to obtain a nonionic polymer emulsion.
14. The preparation method according to claim 13, characterized in that: The polymer precursor particles, the ethoxy-containing polymer and the initiator are mixed in a ratio of (300 to 400): (90 to 125): (20 to 50); and / or The material of the polymer precursor particles includes at least one of polystyrene, polyolefin, polyimide, melamine resin, phenol resin, cellulose, polyester, polyphenylene sulfide, polyaramid, polyamideimide, and copolymer of butyl acrylate and ethyl methacrylate; and / or The ethoxy-containing polymer comprises at least one of allyl polyethylene glycol and bisallyl polyether; and / or The initiator comprises at least one of di-tert-butyl peroxide and dicumyl peroxide; and / or The reaction temperature is 130°C to 140°C; and / or The polymer particles and the nonionic surfactant are emulsified in a mass ratio of (4 to 6):
1.
15. The preparation method according to claim 13 or 14, characterized in that: The nonionic polymer emulsion satisfies at least any one of the following conditions (1) to (4): The nonionic polymer emulsion satisfies at least one of the following conditions (1) to (5): (1) The viscosity of the polymer particle nonionic emulsion at 25° C. is 10 mPa·s to 100 mPa·s; (2) the solid content of the polymer particle nonionic emulsion is 35 wt % to 40 wt %; (3) the pH value of the polymer particle nonionic emulsion is 5 to 6; and / or (4) The nonionic surfactant includes a molecular structure of Wherein, R1 is a carbon chain alkyl group, R2 is a hydrophilic group, and n is a positive integer from 3 to 20.
16. The preparation method according to claim 15, characterized in that: The carbon chain alkyl is a long carbon chain alkyl of C12 to C18; and / or The R2 is at least one of a carboxyl group, an amine group, an aldehyde group, an alcohol group, an amino group, and an amide group.
17. The preparation method according to any one of claims 13 to 16, characterized in that: The nonionic surfactant includes at least one of fatty alcohol polyoxyethylene ether, alkylphenol polyoxyethylene ether, fatty acid polyoxyethylene ester, castor oil polyoxyethylene ether, fatty amine polyoxyethylene ether, sorbitan fatty acid ester and polyoxyethylene sorbitan fatty acid ester.
18. The preparation method according to any one of claims 12 to 17, characterized in that: The aqueous binder is added in the form of a binder aqueous solution, and the binder aqueous solution has at least one of the following conditions: The viscosity of the binder aqueous solution at 25° C. is 3000 mPa·s to 10000 mPa·s; The solid content of the binder aqueous solution is 40 wt % to 50 wt %.
19. The preparation method according to any one of claims 11 to 18, characterized in that: The coating slurry is applied at a rate of 20 m / min to 100 m / min; and / or The drying temperature is 50°C to 70°C; and / or The drying time is 1 min to 5 min.
20. A battery, characterized in that: The invention comprises a positive electrode, a negative electrode and a separator stacked between the positive electrode and the negative electrode, wherein the separator is the separator according to any one of claims 1 to 10 or a separator prepared by the preparation method according to any one of claims 11 to 19.
21. The battery according to claim 20, characterized in that The coating layer is disposed on one surface of the separator, and the coating layer faces the negative electrode.
22. An electrical device, characterized in that: The electrical device comprises the battery as claimed in claim 20 or 21, and the battery is used to provide electrical energy.